Cardiac involvement and superior vena caval obstruction in Behçet's disease. Issue 3 (June 1978) - Roguin, N; Haim, S; Reshef, R; Peleg, E; Riss, E
Abstract : A patient with Behçet's disease developed the rare complications of pericarditis and, two months later, superior vena caval obstruction. The latter complication was investigated by angiography to exclude other causes. As a result of this investigation the caval obstruction was managed conservatively, the symptoms and signs improving spontaneously.